Antibiotic Treatments and Patient Outcomes in Necrotizing Enterocolitis - Murphy, Catherine; Nair, Jayasree; Wrotniak, Brian; Polischuk, Emily; Islam, Shamim (American Journal of Perinatology, 2019)
Objective This study aimed to examine the impact of different antibiotic treatments on necrotizing enterocolitis (NEC) outcomes.Study Design Patient outcomes, including total parenteral nutrition and hospitalization durations, abdominal surgeries, intestinal strictures, and mortality data, were analyzed and compared by various antibiotic groups and treatment durations for 160 NEC patients managed at the Women and Children's Hospital of Buffalo between 2008 and 2016.Results Fourteen different antibiotics were used for NEC, most commonly ampicillin, gentamicin, and metronidazole (AGM). Medical (vs. surgical) NEC patients more likely received AGM (37 vs. 6%, p < 0.001). Surgical (vs. medical) NEC patients more likely received vancomycin (80 vs. 30%, p < 0.001) and antipseudomonal agents (69 vs. 15%, p < 0.001). For medical NEC there were no outcome differences between patients receiving only AGM versus those receiving other treatments; in patients receiving AGM, there were no outcome differences in durations of ≤10 days versus longer courses.Conclusion Antibiotic use for NEC varies substantially without definite outcome differences. Particularly with medical NEC, AGM for ≤10 days had comparable outcomes to other treatments. In light of growing concern for short and longer term adverse effects with early-life antibiotic exposure, narrow-spectrum and shorter course NEC treatment may be preferred.
Keywords: necrotizing enterocolitis; antibiotics; antibiotic management for NEC